Implementation of Research-Based Learning for Prospective Physics Teachers: A Case Study - Handina Handina; Siti Nurul Khotimah (Journal of Science Learning, 2023)
Prospective physics teachers must have research skills because they will later utilize and transfer these skills throughout their teaching careers. However, research shows that students' research skills, including in Indonesia, are still low. In addition to equipping students with theoretical research knowledge, an emphasis is needed on the practical stage for prospective teachers in obtaining research skills. Using a reflective case study approach with qualitative methods, this research observes and describes the implementation of research-based learning for prospective physics teachers. The research-based learning was implemented through an experiment on resistance utilizing alternative tools and materials. Data was collected through participant observation from four participants, with the researcher as the main instrument. This study shows that the implementation of research-based learning provides an opportunity for prospective physics teachers to practice research skills and apply the scientific method to solve problems. More studies are needed regarding implementing research-based learning, especially in higher education.